2023
DOI: 10.1088/1402-4896/ad1150
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of perfect Laguerre–Gaussian entangled states in non-Kolmogorov atmospheric turbulence

Xiaotong Yu,
Ziqing Yin,
Jicheng Wang
et al.

Abstract: We investigate the impacts of backward scattering (BS) of non-Kolmogorov turbulence on the entangled perfect Laguerre–Gaussian (PLG) beams. The explicit expressions for PLG quantum entanglement and quantum coherence are derived in the BS case. We find that the introduction of BS reduces the entanglement and coherence, disrupts the initial decay characteristics, and induces the revival of entanglement and coherence, in which sense turbulence may possess a non-Markovian (memory) effect. As the OAM number increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Underwater wireless optical communication (UWOC), which has the advantages of large bandwidth, high transmission rate and good confidentiality, has attracted the attention of a wide range of researchers [1,2]. Vortex beams, characterized by their possession of orbital angular momentum (OAM), with each photon carrying an OAM value of m 0 ÿ, where unlimited index m 0 represents the topological charge and ÿ is reduced Planck constant, can provide another degree of freedom for multiplexing applications due to the orthogonality among different OAM indexes [3][4][5][6][7][8]. It has been shown that the OAM multiplexing technique can significantly enhance the transmission efficiency of UWOC systems [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Underwater wireless optical communication (UWOC), which has the advantages of large bandwidth, high transmission rate and good confidentiality, has attracted the attention of a wide range of researchers [1,2]. Vortex beams, characterized by their possession of orbital angular momentum (OAM), with each photon carrying an OAM value of m 0 ÿ, where unlimited index m 0 represents the topological charge and ÿ is reduced Planck constant, can provide another degree of freedom for multiplexing applications due to the orthogonality among different OAM indexes [3][4][5][6][7][8]. It has been shown that the OAM multiplexing technique can significantly enhance the transmission efficiency of UWOC systems [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%